Ghanaian men and the performance of masculinity: negotiating gender-based violence in postcolonial Ghana - Dery, Isaac (Gender Studies, 2018)
Within contemporary scholarship on formations of gender and their connections to violences, important questions concerning the politics of masculinities arise. Leading scholars, such as Kopano Ratele, argue for African contexts to be theorized beyond frameworks developed by scholars such as Connell, Kimmel, and Messerschmidt, whose research is grounded in work outside the continent's histories. At the same time, many scholars and policy-makers share the recommendation that global goals for a sustainable world-order demand the reduction of violence, especially violence against women and girls. Masculinities scholarship has, overall, explored the meaning of violence against women for diverse masculine constituencies in much less depth than it has engaged questions of the constructions of hegemonies, the experiences of violence within men's own lives, and the impact of changing economic and political orders on constructions of masculinity. This thesis seeks to address the gap between theorization on masculinity which respects diversity and complexity and theorization on violence against women, particular intimate partner violence within marriage, which tends to imagine a homogenous perpetrator: husband. It is vitally important to investigate and contextualize the discourses of people gendered as 'men', within very specific contexts, to explore the connections made between 'becoming men' and the meaning of domestic violence in their own spaces. Of particular focus in this thesis is an interrogation of the place of domestic violence in men's social worlds. The thesis contributes to knowledge on masculinities by offering an unusually detailed set of culturally sensitive and contextual insights into the social world that is iteratively navigated by married men in a manner to gain recognition as credible, a world in which previous research has already revealed to include women's experiences of abuse, discrimination, and stigma from their husbands. The thesis uses qualitative methods to generate material from men in north-western Ghana through in-depth interviews and focus group sessions. The work takes as a useful entry point the lived experiences, language, and vernacular understandings of people who are, in twenty-first century Ghana, legally criminalized for domestic violence. While such criminalization is welcome, from diverse points of view, the research undertakes a complex qualitative search into how possible 'perpetrators' themselves construct the connection between masculinity, the contemporary socio-economic order, and violence against women, especially wives. The material is analyzed intensively through thematic discourse analysis, and the argument overall is that that violence against wives is discursively connected to how the 'states' and 'citizens' discursively construct masculinity, femininity, and the credibility of violence within a larger gender-nation battle. The analysis simultaneously reveals a dramatic distinction between the construction of violence against wives as legitimate 'correction' (something far from a criminal court) and its construction as 'abusive,' and thus potentially actionable. This distinction alone deepens an understanding of the difficulty of implementing any Domestic Violence Acts, and also leads to questions about the construction of homosociality as a zone of safety and status, one threatened by behaviour from twenty-first century wives. This thesis both confirms earlier research on masculinities and domestic violence in its clear revelation of discursive collusion between men on the appropriate forms of disciplining intimate partners, and also suggests some debate in this collusion. The overarching contribution of the research comes in its argument that the possibility of domestic violence is embedded within contemporary meanings for masculinity, wifehood, marriage and the nation.